A broadly effective vaccine against porcine post-weaning diarrhea - Lu, Ti (Kansas State University, 2019)
Enterotoxigenic Escherichia coli are the major causes of porcine post-weaning diarrhea (PWD). Currently, no licensed vaccines for ETEC exist. However, studying ETEC helps to better understand the role of these organelles in biology and pathogenesis, opens a new door to disease diagnosis, prevention and treatment, and enables development of effective vaccines. In Chapter 2, the study was focused on mapping the immuno-dominant or neutralizing epitopes from the adhesive subunit FedF of F18 fimbriae. Our data showed that seven immune-dominant epitopes were identified from FedF subunit. Epitope fusions induced anti-F18 antibodies in subcutaneously immunized mice. Moreover, antibodies derived from each fusion significantly blocked adherence of a F18-fimbrial E. coli bacteria to pig intestinal cell line IPEC-J2. While all seven epitopes exhibited neutralizing activity, results from this study identified FedF epitopes #3 (IPSSSGTLTCQAGT) and #7 (QPDATGSWYD) as the most effective for antibodies against F18 fimbrial adherence and suggested their future application in PWD vaccine development. In Chapter 3, we further identified B-cell immunodominant epitopes from K88 fimbrial major subunit (also adhesin) FaeG. We found that while all nine FaeG epitope fusions induced antibodies to K88 fimbria, anti-K88 IgG antibodies derived from epitopes #1 (MTGDFNGSVD), #2 (LNDLTNGGTK), #3 (GRTKEAFATP), #4 (ELRKPDGGTN), #5 (PMKNAGGTKVGAVKVN) and #8 (RENMEYTDGT) significantly inhibited adherence of K88-fimbrial bacteria to porcine intestinal cell line IPEC-J2, indicating the ability of these peptides to neutralize EPITOPES of K88 fimbrial major subunit FaeG and suggesting the future application of FaeG epitopes in ETEC vaccine development. In Chapter 4, a PWD multiepitope fusion antigen (PWD-MEFA) was constructed. Our data showed the expressed fimbriae-toxoid PWD MEFA protein, which was approximately 40 kDa, was verified in Western blot analysis using anti-FaeG, anti-K88epitope-fusion, anti-F18epitope-fusion, anti-CT, anti-STa, and anti-Stx2e antiserum, respectively. Mice SC immunized with PWD MEFA protein developed strong anti-K88, anti-F18, anti-LT and anti-STb IgG antibody responses, and moderate anti-Stx2e and anti-STa IgG responses. Moreover, mouse serum antibodies inhibited adherence of K88- and F18-fimbrial ETEC bacteria and neutralized LT, STa, STb and Stx2e enterotoxicity. Additionally, double mutant LT (dmLT, LT subscript(R192G/L211A)) adjuvant up-immunoregulated PWD MEFA anti-fimbriae and antitoxin antibody responses. These results indicated that this fimbriae-toxoid PWD MEFA induced broadly anti-fimbriae and anti-toxin antibodies, and suggested antigen candidacy for developing an effective vaccine against PWD. In Chapter 5, we optimized this MEFA to be expressed as a holotoxin-structured and GM1-binding protein in a live host strain to induce mucosal antibodies against ETEC adhesins and toxins. Our data showed that optimized PWD adhesin-toxoid MEFA formed a holotoxin structure and bound to GM1 receptor, and Salmonella Ty21a strain, as well as porcine field E. coli isolate G58 to produce the new adhesin-toxoid MEFA and secreted the protein outer-membrane. These results suggest that Ty21a or G58 host producing the GM1-binding adhesin-toxoid MEFA can potentially be an effective mucosal vaccine against PWD. In summary, this study investigated the immunodominate and neutralizing epitopes of F18 fimbrial adhesin subunit FedF and K88 fimbrial adhesin subunit FaeG, and also constructed and optimized a PWD fimbriae-toxoid MEFA inducing broadly effective protection against PWD-associated ETEC infection.
Keywords: Post-weaning diarrhea; Pig; Vaccine; ETEC